Willingness-to-pay and free-riding in a national energy efficiency retrofit grant scheme. (July 2018) - Collins, Matthew; Curtis, John
Abstract: Many national grant aid schemes exist to encourage households to invest in residential energy efficiency retrofits, but these can also be availed of by free-riders, which are households that would invest in a retrofit even in the absence of financial support. We use a McFadden's choice model to estimate willingness-to-pay for energy efficiency using data from a national residential energy efficiency grant scheme, estimating average marginal willingness-to-pay of €0.127 / kWh / yr for retrofits that affect the efficiency of energy use required for space and water heating (e.g. boiler upgrades, heating controls). The results of this analysis are used to estimate the extent to which free-riding has occurred in the scheme. Less efficient and larger households are willing to pay more for energy efficiency improvements, while households that had previously retrofitted via the scheme were willing to pay over twice as much as those retrofitting for the first-time. Free-riding varies by retrofit measure, with solar collector retrofits possessing close to zero free-riders, while free-riders comprised over 33% of heating controls retrofits. Abstract : Highlights: National grant scheme for residential energy efficiency retrofits. Estimate willingness-to-pay (WTP) for energy efficiency - €0.127/kWh/m2/yr. Compare WTP with investment costs to examine level of free-riding. Overall, free-riding is relatively low compared to prior literature.